Feedback, individual differences and EFL learners productive skill: an analysis on high and low-achieving students - Nasmilah Nasmilah; Sitti Sahraeny; Marleiny Radjuni; Nadira Mahaseng; Sukmawaty Sukmawaty (MAGISTRA, 2021)
This study investigates how feedback is responded by learners of English as a Foreign Language (EFL) having distinctive individual differences, and how these two relate to their achievement in their Speaking ability as productive skill. A group of English Department students at Hasanuddin University comprising high achievers and low achievers is observed in an attempt to collect as much information as possible to get clearer picture of the role of feedback as the second source of input after the teaching materials presented earlier in class. Using descriptive qualitative method in analyzing the data, the study reveals that teachers’ feedback as source of input plays important roles in helping learners gain better performance in speaking skills. However, in some cases, negative effect of feedback is suffered by certain students which lead to the conclusion that individual differences and teachers’ feedback are detrimental in the achievement of EFL learners speaking performance